Exploring the Concepts of Traditional Inuit Leadership and Effective School Leadership in Nunavut (Canada) - Preston, Jane P; Claypool, Tim R.; Rowluck, William; Green, Brenda (Scholarship@Western, 2015)
The purpose of this paper is to document how educators living in Nunavut communities describe traditional Inuit leadership and effective school leadership. The data for this qualitative study were 24 semi-structured interviews, involving 14 teachers, vice-principals, and principals from Nunavut. Findings revealed that traditional Inuit leadership was about promoting the personal leadership skills, interests, and/or abilities of each community member, and it often involved Elders who fostered the linguistic, social, cultural, and spiritual wellness of students and school staff. Participants depicted an effective school leader to be someone who promoted teamwork. Also, participants indicated that effective school leaders were community and people-focused. The findings of this study align the Inuit Qaujimajatuqangit (IQ) principles, which incorporate important features of the Inuit worldview.